Selective cytotoxicity of PAMAM G5 core-PAMAM G2.5 shell tecto-dendrimers on melanoma cells - Schilrreff, Priscila (2012)
The controlled introduction of covalent linkages between dendrimer building blocks leads to polymers of higher architectural order known as tecto-dendrimers. Because of the few simple steps involved in their synthesis, tecto-dendrimers could expand the portfolio of structures beyond commercial dendrimers, due to the absence of synthetic drawbacks (large number of reaction steps, excessive monomer loading, and lengthy chromatographic separations) and structural constraints of high-generation dendrimers (reduction of good monodispersity and ideal dendritic construction due to de Gennes dense-packing phenomenon). However, the biomedical uses of tecto-dendrimers remain unexplored. In this work, after synthesizing saturated shell core–shell tecto-dendrimers using amine-terminated polyamidoamine (PAMAM) generation 5 (G5) as core and carboxyl-terminated PAMAM G2.5 as shell (G5G2.5 tecto-dendrimers), we surveyed for the first time the main features of their interaction with epithelial cells.